Effect of Air Humidity, Wind Speed and Sea Surface Temperature on Rainfall in Bengkulu City - Gita Rahma Sari; Johan, Septi; Supiyati; Anwar, Anang (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2025)
Rainfall is a vital climate component and its variability in equatorial regions such as Indonesia. Bengkulu City, with its strategic geographical position on the edge of the Indian Ocean, is influenced by global and regional climate, as well as local conditions such as topography and sea surface temperature. Air humidity is known to be significantly correlated with extreme rainfall, while wind speed plays a role in air convergence and cloud formation. Therefore, this research tends to examine the air humidity, wind speed and sea surface temperature’s influence on rainfall in Bengkulu City. The method employed in this research is quantitative technique with multiple linear regression analysis using SPSS model. The data employed are monthly data of air humidity, wind speed, sea surface temperature, and rainfall from 2003 to 2023. As model validation before regression analysis, normality and multicollinearity tests were conducted. The analysis outcomes present that air humidity has a significant and positive partial effect on rainfall, which is consistent with its role in the condensation process and cloud formation. In contrast, wind speed and sea surface temperature show no significant partial influence on rainfall. However, simultaneously, these three independent variables (air humidity, wind speed and sea surface temperature) have a significant effect on rainfall. The regression model was able to explain about 63.8% of the variation in rainfall, confirming that air humidity is the main predictor of rainfall in the Bengkulu region.